A new model of criminal intelligence in the Slovak Republic - Jozef Stieranka; Adrián Vaško (DANUBE: Law, Economics and Social Issues Review, 2020)
The purpose of this article is to examine the issue of criminal intelligence in the Slovak Republic with emphasis on determining its functionality and whether it reflects the requirements formulated in the European models of criminal intelligence. The authors comprehensively examine the current legislation in the subject area in the Slovak Republic. The paper is a partial output from the realized scientific research task VYSK. no. 231 'National Model of Criminal Intelligence Service in the Slovak Republic'. The authors came to the conclusion that the current legal regulation of criminal intelligence in the Slovak Republic is not in line with the recommendations of the European Criminal Intelligence Model. In this context, it can be expected that it will be necessary to adopt legislative changes and accept the authors' proposed New Concept of Criminal Intelligence in order to align the criminal intelligence system with the recommendations of the European Union institutions.
Keywords: 330; Operative-investigative Activity; Means of Operative-investigative Activity; Criminal Intelligence; Crime Detection